Exosomes released from M2 macrophages transfer miR‐221‐3p contributed to EOC progression through targeting CDKN1B - Xiaoduan Li; Meiling Tang (2020)
In contrast to other solid tumors within the abdominal cavity, epithelial ovarian cancers (EOCs) tend to undergo peritoneal metastasis. Thus, the peritoneal immune microenvironment is crucial for EOC progression. Previous reports indicate that the main immune cells within the peritoneum are M2 macrophages, specifically tumor-associated macrophages (TAMs). The communication between TAMs and tumor cells plays an important role in EOC development, and exosomes, acting as micro-message carriers, occupy an essential position in this process. Microarray analyses of exosomes revealed that miR-221-3p was enriched in M2 exosomes. Furthermore, miR-221-3p suppressed cyclin-dependent kinase inhibitor 1B (CDKN1B) directly. Thus, miR-221-3p contributed to the proliferation and G1/S transition of EOC cells. Additionally, low levels of CDKN1B were associated with EOC progression and poor prognosis. These observations suggest that TAMs-derived exosomal miR-221-3p acts as a regulator of EOC progression by targeting CDKN1B. The results of this study confirm that certain exosomal microRNAs may provide novel diagnostic biomarkers and therapeutic targets for EOC.